2018
DOI: 10.1152/ajpcell.00339.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide stimulates BK channel activity in bladder umbrella cells

Abstract: Bladder urothelium plays an active role in response to bacterial infection. There is little known about the electrophysiological activity in urothelial cells in this process. We used a nonenzymatic method to isolate bladder urothelial tissue and to patch clamp umbrella cells in situ. A 200 pS conductance potassium (K) channel was detected from female C57BL6 mice. Of 58 total patches, 17.2% patches displayed the 200 pS K conductance channel. This K conductance channel showed Ca sensitivity and voltage dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The translational relevance of these findings is that ERβ, and not ERα, is the estrogen receptor found in the bladder urothelium from female human subjects [ 26 ], and therefore, urothelial ERβ may play a more important role than ERα in UTI pathogenesis in women. A recent publication detected the presence of calcium-activated, voltage-gated, large conductance potassium channel (BK channel) on the umbrella urothelial cells [ 27 ]. Furthermore, urothelial BK channels were opened (activated) by lipopolysaccharides (LPS) suggesting that BK may work the same way in the urothelial cell as in macrophages where BK was important in regulating cytokine release when macrophages were exposed to LPS [ 28 ].…”
Section: Cell Populations In or Associated With The Lutmentioning
confidence: 99%
“…The translational relevance of these findings is that ERβ, and not ERα, is the estrogen receptor found in the bladder urothelium from female human subjects [ 26 ], and therefore, urothelial ERβ may play a more important role than ERα in UTI pathogenesis in women. A recent publication detected the presence of calcium-activated, voltage-gated, large conductance potassium channel (BK channel) on the umbrella urothelial cells [ 27 ]. Furthermore, urothelial BK channels were opened (activated) by lipopolysaccharides (LPS) suggesting that BK may work the same way in the urothelial cell as in macrophages where BK was important in regulating cytokine release when macrophages were exposed to LPS [ 28 ].…”
Section: Cell Populations In or Associated With The Lutmentioning
confidence: 99%
“…Nine animals underwent sham and nine underwent OVX surgery. Four weeks after surgery, bladder urothelial tissues devoid of lamina propria were harvested ( n = 3 sham, n = 3 OVX mice) using the published technique . This was the “post‐surgery” or day 0 time point.…”
Section: Methodsmentioning
confidence: 99%
“…Four weeks after surgery, bladder urothelial tissues devoid of lamina propria were harvested (n = 3 sham, n = 3 OVX mice) using the published technique. 10 This was the "post-surgery" or day 0 time point. Intravesical LPS was instilled using the same protocol as shown in Figure 1 and urothelial tissues were harvested after LPS treatment on day 1 (n = 3 sham, n = 3 OVX mice) and on day 3 (n = 3 sham, n = 3 OVX mice).…”
Section: Urothelial Microarray Analysismentioning
confidence: 99%
“…Protocols PBS, LPS, and IBTX ϩ LPS were performed on another set of n ϭ 12 mice (4 for each protocol). After urine was collected at 2 h, the animals were euthanized, and a sheet of pure bladder urothelial tissue, free of lamina propria and detrusor, was harvested following the published protocol (14) and processed for qPCR experiments. These three inflammatory biomarkers were chosen because all three were significantly elevated after both LPS and UPEC exposure, and, furthermore, the elevations of these three cytokines/chemokines were also significantly blocked by IBTX for both LPS-and UPEC-exposed mice.…”
Section: Urothelial Tissue Dissection and Qpcr For Interleukin-6 Intmentioning
confidence: 99%
“…A recent publication demonstrated that, not only was calcium-activated voltage-gated potassium channel (BK channel) detected in the mouse umbrella cells, but BK channel activity (probability of open BK channel) was significantly increased by LPS exposure (14), suggesting that urothelial BK has a potential role in UTI pathogenesis. The role of BK in innate immune response has been shown in macrophages.…”
Section: Introductionmentioning
confidence: 99%